The problem of the „Thomas Nagel’s Bat" in the Argumentation of John Hick and Paul M. Churchland. - Strzyzynski, Przemyslaw (Filozofia Chrześcijańska, 2010)
The article tries to show the relations between P. M. Churchland's and J. Hick's reference to T. Nagel's „bat argument" and is based on Nagel's, Mortal questions, Chuchralnd's The Engine of Reason, the Seat of the Soul. A Philosophical Journey into the Brain and J. Hick's The New Frontier of Religion and Science. Religious experience, neuroscience and the transcendent. The clue is that Churchland and Hick beg the main point of the Nagel's argument about the difference between mind and brain. Churchland agrees with Nagel in assuming of the self and only self knowledge about mind states. But the former author and Hick misunderstand that indeed Nagel argues that it is still impossible to identify subjective states as objective. Moreover, Hick avoids Churchland's counter-argument. Therefore, not all of the dispute concerns the same problem.